The DiabEase initiative empowering diabetes management during Ramadan / Saliha Azlan and Gurmeet Kaur Surindar Singh - Azlan, Saliha; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2025)
Diabetes management presents unique challenges during Ramadan, particularly for individuals who observe fasting. In Malaysia, where a substantial segment of the population participates in this practice, effective managing medication and maintenance of glycaemic control are essential. In response to this issue, a research team from the Faculty of Pharmacy, UiTM Puncak Alam, has initiated a project to develop a mobile application titled DiabEase.